Racial/Ethnic Differences in the Relationship Between Parental Education and Substance Use Among U.S. 8th-, 10th-, and 12th-Grade Students: Findings From the Monitoring the Future Project - Bachman, Jerald G. (Rutgers University, 2011)
OBJECTIVE: Secondary school students' rates of substance use vary significantly by race/ethnicity and by their parents' level of education (a proxy for socioeconomic status). The relationship between students' substance use and race/ethnicity is, however, potentially confounded because parental education also differs substantially by race/ethnicity. This report disentangles the confounding by examining White, African American, and Hispanic students separately, showing how parental education relates to cigarette smoking, heavy drinking, and illicit drug use. METHOD: Data are from the 1999-2008 Monitoring the Future nationally representative in-school surveys of more than 360,000 students in Grades 8, 10, and 12. RESULTS: (a) High proportions of Hispanic students have parents with the lowest level of education, and the relatively low levels of substance use by these students complicates total sample data linking parental education and substance use. (b) There are clear interactions: Compared with White students, substance use rates among African American and Hispanic students are less strongly linked with parental education (and are lower overall). (c) Among White students, 8th and 1 0th graders show strong negative relations between parental education and substance use, whereas by 12th grade their heavy drinking and marijuana use are not correlated with parental education. CONCLUSIONS: Low parental education appears to be much more of a risk factor for White students than for Hispanic or African American students. Therefore, in studies of substance use epidemiology, findings based on predominantly White samples are not equally applicable to other racial/ethnic subgroups. Conversely, the large proportions of minority students in the lowest parental education category can mask or weaken findings that are clearer among White students alone.